Case Report: New CDKN1B Mutation in Multiple Endocrine Neoplasia Type 4 and Brief Literature Review on Clinical Management - Lavezzi, Elisabetta; Brunetti, Alessandro; Smiroldo, Valeria; Nappo, Gennaro; Pedicini, Vittorio; Vitali, Eleonora; Trivellin, Giampaolo; Mazziotti, Gherardo; Lania, Andrea (Frontiers in Endocrinology, 2022)
Background: The fourth type of Multiple Endocrine Neoplasia (MEN) is known as a rare variant of MEN presenting a MEN l-like phenotype and originating from a germline mutation in CDKN1b. However, due to the small number of cases documented in literature, the peculiar clinical features of MEN 4 are still largely unknown, and clear indications about the clinical management of these patients are currently lacking. In order to enlarge our knowledge on MEN 4 and to better typify the clinical features of this syndrome, we present two more cases of subjects with MEN 4 and, through a review of the current literature, we provide some possible indications on these patients' management. Case presentation: The first report is about a man who was diagnosed with a metastatic ileal G2-NET.at the age of 34. Genetic analysis revealed the mutation p.I119T (c.356T>C) of exon 1 of CDKN1b, a mutation already reported in literature in association with early-onset pituitary adenomas. The second report is a 76-year-old woman with a multifocal pancreatic G1-NET. Genetic analysis identified the CDKN1b mutation c.482C>G (p.S161C), described here for the first time in association with MEN 4 and currently classified as a variant of uncertain significance. Both patients performed biochemical and imaging screening for MEN1-related diseases without any pathological findings. Conclusions: According to cases reported in literature, hyperparathyroidism is the most common clinical feature of MEN 4, followed by pituitary adenoma and neuroendocrine tumors. However, MEN4 appears to be a variant of MEN with milder clinical features and later onset. Therefore, these patients might need a different and personalized approach in clinical management and a peculiar screening and follow up strategy